Engaging in Prosocial Behaviour for an Inclusive Society (IntechOpen, 2025)
Engaging in Prosocial Behaviour for an Inclusive Society offers an essential exploration of how educational institutions can foster inclusivity, prosocial behavior, and community engagement. In today’s world, marked by global diversity, social fragmentation, and complex environmental challenges, the need for transformative approaches in education has never been greater. This book brings together a collection of innovative research and insights that delve into trauma-informed teaching, culturally responsive pedagogy, diversity training, and sustainability education, highlighting the vital role of education in shaping equitable and compassionate societies. Designed for educators, researchers, and policymakers, the book provides practical frameworks for developing inclusive learning environments that promote empathy, equity, and active citizenship. Readers will gain a deeper understanding of how trauma-aware practices, transformative learning, and community-based engagement can help address systemic inequalities and promote social justice. Through a blend of theoretical perspectives and real-world applications, Engaging in Prosocial Behaviour for an Inclusive Society emphasizes the importance of cultivating inner capacities such as self-awareness, mindfulness, and intercultural understanding, which are critical for building connections across diverse groups. By focusing on both individual development and institutional transformation, this book empowers educators and students alike to take meaningful action in creating a more inclusive and sustainable future. It offers actionable strategies to support prosocial behavior and community engagement within higher education, aiming to prepare the next generation of leaders to engage positively with their communities and the world. Whether you are an educator, administrator, or researcher, this book provides invaluable insights and tools to shape transformative educational practices that lead to lasting social impact.